ADMINISTRATION AND REGULATION OF WATER SUPPLY AND SANITATION SERVICE SECTOR OF UKRAINE - Iryna Krylova (World Science, 2019)
The article deals with the sphere of services of water supply and sanitation of Ukraine as an object of public administration and regulation. The meaning of the notions "drinking water", "drinking water supply", "centralized water supply", "wastewater (sanitation)" and others are provided. The composition of water supply and sanitation services is analyzed. The questions of surface wastewater (water received and collected in the form of atmospheric precipitation), which are not included in the list of water supply and sanitation services, are considered. Modern models of management of enterprises of water supply and sanitation in Ukraine are considered, the overwhelming majority of which is direct communal management. The legal status and features of water supply and sanitation companies of communal property are determined. The peculiarities of realization of public-private partnership in the field of water supply and wastewater are considered, examples of existing lease / concession agreements of water supply and sanitation facilities are given. The legal principles of state regulation of the activities of water supply and sanitation enterprises and regulatory measures are considered. The legal principles and features of the state tariff policy in the field of water supply and wastewater are determined. The issues of quality of water supply and sanitation services, consumer rights protection and environmental regulation in the field of water supply and wastewater are considered.